GAMBARAN SANITASI LINGKUNGAN MASYARAKAT TERHADAP KEJADIAN DBD DI RW 11 KELURAHAN SIDOMULYO TIMUR KECAMATAN MARPOYAN DAMAI PEKANBARU - - Chairil; Azril Dames (LPPM Universitas Muhammadiyah Riau, 2017)
Dengue Fever (DHF) is a public health problem, in 2016 dengue cases continue to rise in the city of Pekanbaru, this led to some villages in the city of Pekanbaru including dengue endemic area. The purpose of this study was to determine the Community Environmental Sanitation Overview Of Genesis Dengue Hemorrhagic Fever (DHF) in RW 11 Sub Sidomulyo Eastern District of Marpoyan Peace Pekanbaru. This type of research accidental sampling. Methods using questionnaires and interviews were held on July 15, 2016 21-, 80 respondents. Results penelitiann not experienced DHF 97.5% on good sanitation and 58 environmental samples and on the category of poor environmental sanitation contained 22 samples with a total of 80 samples. As for sanitation affected by dengue in a good environment no (free DBD) and the poor environmental sanitation as many as 2 respondents (2.5%). This shows a good picture ofenvironmental sanitation reduced the risk of incidence of dengue and vice versa with a picture of poor environmental sanitation potentially affected by dengue. There is a link between the incidence of dengue with environmental sanitation.